ANALISIS KUAT TEKAN DAN KUAT TARIK BELAH PADA BETON DENGAN PENAMBAHAN SERAT SERABUT KELAPA DAN BATU APUNG - Ade Okvianti; Liastary Pradina Febrianty (Universitas Trisakti, 2022)
ABSTRACT The use of added materials from natural as a mixture of concrete is growing and varied. In this study, researchers used coconut fiber and pumice stone (pumice) as a concrete mixture to reduce the weight of the concrete so that it became lighter. This test aims to determine the effect of adding pumice stone as a partial substitution with the addition of coconut fiber on the mechanical characteristics of concrete that is the compressive strength and the split tensile strength of concrete. Pumice, which is as much as 20%, is used as a partial replacement of the weight of coarse aggregate with the addition of coconut fibers which are used at 0%, 0.5%, 1%, 1.5% and 2% of the weight of cement as a mixture in concrete. The test was carried out on cylindrical specimens measuring 100 x 200 mm which included compressive strength and splitting strength at 28 days. From the test results, it was found that the compressive strength decreased from 20.97 MPa for normal concrete without the addition of pumice and fiber to 15.45 MPa for concrete with partial substitution of pumice, while with the addition of the percentage of coconut fibers, the compressive strength obtained was 16.55 MPa, 17.88 MPa, 13.90 MPa and 14.57 MPa. In this study, the split tensile strength was also tested and it was found that the split tensile strength increased successively with the optimum tensile strength in concrete with the addition of 2% coconut fiber, namely 1.78 Mpa. Keywords : Pumice, Concrete, Partial Substitute, Coconut Fiber